Hz. Peygamber’e yönelik emir ve nehiyler bağlamında Kur’ân-sünnet ilişkisi - Ghudaya, Abubaker (My University, 2019)
“Hz. Peygamber’e Yönelik Emir ve Nehiyler Bağlamında Kur’ân-Sünnetİlişkisi” adlı bu tez efendimize hitaben gelen emir ve yasakları ele almakta ve bunlarınsünnetteki uygulamalarını incelemektedir. Bu çalışma, söz konusu mühim meseleyi şuana kadar hiçbir şekilde örneği olmayan bir yolla ele almaktadır. Kur’ân ve sünnetilişkisine dair konuları bu çalışmada olduğu gibi tek bir yerde toplayan başka biraraştırma söz konusu olmamıştır. Aynı şekilde zikredilen konu, Kur’ân’da Hz.Peygamber’e yönelik gelen emir ve yasakların bizzat Hz. Peygamber tarafından nasıluygulandığının ele alınması açısından da ilk defa bu şekilde ortaya konmaktadır.Araştırmada şu meselelerin açıklanması hedeflenmektedir: Kur’ân ve sünnet ilişkisi,Sünnetin Kur’ân’a göre konumu, Kur’ân’ın sünneti takyit, tahsis yahut tekit ettiğidurumlar, Kur’ân’ın sünnete olan ihtiyacı ve sünnetin Kur’ân ışığında anlaşılması. Aynışekilde Kur’ân’daki emir ve nehiylerin kapsamlı bir tanımı yapılmak suretiyle bunlarınsünnetle ilişkisi, emir ve nehiy kalıplarının belirlenmesi, karinenin söz konusu emrinyahut yasağın hükmüne ve gereğine olan etkisi, ve bunların ne derece sünnetle ilintiliolduğu, Kur’ân’da kendilerine hitap edilen kimselerin sınıfları, Hz. Nebî’ye yönelikgelen emir ve nehiylerin aslında kimi muhatap aldığı, bu emir ve yasakların efendimizinismet sıfatıyla olan ilişkisi ve ona hitaben gelen emir ve yasakların hikmeti konuları elealınacaktır. Tüm bu zikredilenleri açıklamak amacıyla efendimizin pratik uygulamalarıortaya konacaktır.Kur’ân-Sünnet ilişkisini, sünnetin Kur’ân’a göre konumunu vehüccet oluşunu ele almakta ve tanımını yapıp Kur’ânî, nebevî ve aklî delillerle bunudesteklemektedir. Kur’ân’ın sünnete olan ihtiyacı, bundan kastedilenin ne olduğu vemutlağı takyit gibi sünnetin Kur’ânla ilişkisindeki durumunun izahı da bu bölümde eleIIalınmaktadır. Aynı şekilde bunun sünnetteki uygulamaları, sünnetin Kur’ân ışığındaanlaşılması ve bundan kastın ne olduğu, Kur’ân’ın sünneti nesh etmesi gibi durumlarıntartışılması da bu bölümde yer almaktadır.İkinci bölüm, Kur’ân’da emir ve nehye taalluk eden ana konular çerçevesindebunların sünnetle ilişkisini ele almaktadır. Bu bölümde, emir ve nehyin mahiyyeti vesîgaları, karinenin emrin gereğine etkisi ve emre ve nehye muhatap olanların tanımıverilmekte bu emir ve yasakların söz konusu kimselerle alakası tartışılmaktadır.Üçüncü bölüm, Hz. Peygamber’e gelen emir ve yasakları doğrudan efendimizinpratiği üzerinden incelemektedir. Bu bölüm, namaz, zekat ve dine da’vet gibi çeşitlibablara bölünmüş ve her babta o konuyla alakalı emir ve yasaklar nüzul sırasına göredercedilmiştir. Emir ve nehyin zikredilmesinin ardından söz konusu emir ve yasaklaradair nebevî uygulamalar belirtilmekte ve bunlardan beklenen fayda ortaya konmaktadır.Son bölümde araştırma sonucu elde edilen önemli sonuçlar zikredilmektedir.Aynı şekilde Hz. Peygamber’e hitaben gelen emir ve yasaklarla ilgili tekrar – tekrarsız,Mekkî-Medenî olmaları gibi durumlar göz önüne alınarak tablolar verilmektedir.Emirlerin yasaklara oranları, Mekkî olanların Medenî olanlara oranları, maksudu veefendimiz gelen emir ve yasaklar ve onunla beraber başkalarını da kapsayanlar yahutsadece başkalarını kapsayanların oranları verilmektedir.

THE QUR’ANİC COMMANDS AND PROHİBİTİONS DİRECTED TO THE PROPHET -PEACE BE UPON HİM - AND THEİR IMPLEMENTATİON İN THE PROPHETİC TRADİTİONThis study explores the commands and prohibitions directed to the ProphetMuhammad in the Qur’an, and the Prophet’s implementation of them in the Sunnah(Prophetic Tradition). Unprecedented in its approach, this study surveys the Qur’an andSunnah concurrently, linking the two together. Never before has a single work compiledan extensive list of topics exclusively on the relationship between the Qur’an andSunnah. This study attempts to do just that, all while highlighting that relationship fromseveral angles, such as: the relationship’s history and development; the Sunnah’s statuswith respect to the Qur’an; the Qur’an’s role vis-à-vis the Sunnah; the Qur’an’s need forthe Sunnah; and understanding the Sunnah in light of the Qur’an. Nor has therelationship between the Qur’an and Sunnah ever been examined through the lens of theQur’anic directives (commands and prohibitions) addressed to the Prophet (pbuh) andtheir corresponding implementations. In an attempt to fill that void, this study details therelationship between the Qur’anic directives and the Sunnah. It includes technicaldefinitions for command and prohibition, linguistic manifestations of both in theQur’an, the effect of a qarīna (context indicator) on a directive’s legal implications, thedegree to which Qur’anic directives are linked to the Sunnah, the recipient classesaddressed by the directives, the intended recipients of the various directives addressedto the Prophet, the relationship between the directives and the doctrine of propheticinfallibility, the wisdom behind the directives addressed to the Prophet, and forclarification purposes, practical examples of everything discussed.IVThis is a systematic study relying on inductive, deductive, analytical, andpragmatic methods. It is divided into an introduction and three sections.The Introduction sets forth the subject matter, methodology, and relevantprevious works.Section I discusses the relationship between the Qur’an and Sunnah by focusingon the status of the Sunnah. Using evidence from the Qur’an and Ḥadīth, and throughrational reasoning, this section demonstrates the Sunnah’s position as an authoritativesource, the Qur’an’s need for the Sunnah, the Sunnah’s role vis-à-vis the Qur’an—suchas in delimiting what appears to be absolute—with supporting examples, in addition toexplaining how the Sunnah is understood in light of the Qur’an, and discussing theQur’an’s role vis-à-vis the Sunnah, such as in its abrogation of the Sunnah. The sectionconcludes with a summary of the main points: (1) the Sunnah is primary authority,second only to the Qur’an; (2) the Qur’an’s need for the Sunnah surpasses the Sunnah’sneed for the Qur’an; and (3) just as the Sunnah plays a role vis-à-vis the Qur’an, so toodoes the Qur’an vis-à-vis the Sunnah.Section II surveys the Qur’anic directives and their relationship with theSunnah. It does so by discussing the Qur’an’s major topics and their relationship withthe Qur’anic directive, the directive’s core definition and linguistic manifestations, theqarīna’s effect on a directive’s legal implications, the relationship between thedirectives—with their various classes of addressees—and the Sunnah, the intendedrecipients of the various directives addressed to the Prophet, the relationship betweenthe directives and the doctrine of prophetic infallibility, and the wisdom behind thedirectives addressed to the Prophet. The section concludes with several takeaway points,foremost of which that the Qur’anic directives fall under and relate to all of the Qur’an’ssubject matters, including its manifest signs, narratives and admonitions; and that,whether they address the Prophet or any other party, the Qur’anic directives areinextricably linked to the Sunnah.Section III examines the commands and prohibitions directed to the Prophet(pbuh) in the Qur’an, and the Prophet’s implementation of them in the Sunnah. Thesection is topically divided into chapters based on traditional Islamic jurisprudentialsubjects such as prayer, alms-giving, and inviting to Islam. Each chapter encompassesthe relevant Qur’anic directives arranged in order of revelation. Each directive, in turn,Vis followed by its corresponding implementation in the Sunnah, an assessment of itsaccord with that implementation, and a review of its utility. Each chapter is furnishedwith a conclusion summarizing its main points. Section III concludes with importanttakeaway points, such as: (1) the majority of Qur’anic directives were revealed duringthe Makkan period, an early stage in the call to Islam naturally requiring more guidance;and (2) while some of the directives were intended for the Prophet alone, others werenot intended for him exclusively, and yet others were not intended for him at all.Conclusion, Appendices, and Indices: The conclusion presents the mostimportant results and offers recommendations. Appendices contain an extensive list ofthe directives addressed to the Prophet, with classifications of Makkan or Madīnan,recurrent or otherwise, and the directives’ intended recipients, with citations. Graphicsare included to clarify matters such as the proportion of Makkan to Madīnan directives,in addition to the percentages of directives intended for the Prophet alone, directivesintended for others alongside the Prophet (pbuh), and directives intended for others tothe exclusion of the Prophet. Finally, an assortment of indices is attached for theresearcher’s convenience.
Keywords: COMMAND; EMİR; İLİŞKİ; İMPLEMENTATİON; KUR’AN; NEHİY QUR’AN; PROHİBİTİON; RELATİON; SUNNAH; SÜNNET; UYGULAMA